The Environmental Analysis of Polymers Process - Altuwair, Ibrahim (Edelweiss Applied Science and Technology, 2018)
The chemical industrial processes with their energy-intensive production methods and unpleasant image have become “business as usual”. Polycarbonate (PC) is one example of energy intensive methods that has become one of the largest industrial processes. Moreover, a large number of hazardous chemicals are used throughout its manufacturing stages. This study is concerned with environmental aspects of PC production. It investigates life cycle based environmental performance evaluation of supercritical fluid (SCF) Application to PC production, more specifically in i) Environmental performance assessment of SFC as chlorinating alternative and ii) Environmental performance assessment of plasticizing scenario as stabilizing step in the PC production. The advantages of using SCF are tied to the cleaner aspects of the technology, minimization of raw materials and energy demand, reduction of emissions and effluent discharge into the environment and maximization of environmental benefits. Environmental performance of polycarbonates production by SCF was compared with that of traditional production methods. It was observed that supercritical fluid technology has an impact on the emissions reduction compared with traditional methods. This research contributes to understanding the challenges that the industry of polycarbonate production will face in the future where the chemical emissions are increased resulting from production and energy consumptions.